The Role of Culture in Shaping Female Characters: A Critical Analysis of Mawar Safei's Selected Short Stories from the Perspective of "Mahabbah" (Malay Literature, 2024)
Culture is an identity formed by members of a society as a reference for intellectual development and is expressed in various forms, including the literature of that society. Accordingly, this study aims to discuss the role of culture in influencing character formation portrayed in Malay literary works. Focusing on female characters, this paper explores Mawar Safei’s tendency to elevate the image of the Malay Muslim woman in her works. This inclination provides justification for the capability of female authors to portray the ideal female Malay character from their own perspective. This is an important topic to address, given previous research findings that tend to align the depiction of female Malay Muslim characters with Western thought models. These findings have sparked a paradigm of reductionism or the neglect of Malay-Islamic philosophical aspects and worldview in discussions of female characters in literary works. Thus, the current study examines the role of culture in shaping female Muslim characters using an analysis framework based on the Islamic concept of Mahabbah (divine love for Allah) to emphasise the author’s commitment to this aspect. The discussion on Malay culture based on the concept of Mahabbah is subsequently focused on three of Mawar Safei’s short stories—Gempa Pulau Perca, Antara Dua Rumah di Lereng Bukit, and Tangan Umi dan Takwil Mimpi—in the short story collection Narasi Tanah Selandia Baru dan Kisah Lainnya (2021). The analysis and findings conclude that the cultural elements used in shaping the female Muslim characters in Mawar Safei’s works reflect the intellectual depth of a female author in guiding the intellectual development of her readers.Full text: PDF